2012
DOI: 10.1177/0960327112440111
|View full text |Cite
|
Sign up to set email alerts
|

Relative trends in hospitalizations and mortality among infants by the number of vaccine doses and age, based on the Vaccine Adverse Event Reporting System (VAERS), 1990–2010

Abstract: In this study, the Vaccine Adverse Event Reporting System (VAERS) database, 1990–2010, was investigated; cases that specified either hospitalization or death were identified among 38,801 reports of infants. Based on the types of vaccines reported, the actual number of vaccine doses administered, from 1 to 8, was summed for each case. Linear regression analysis of hospitalization rates as a function of (a) the number of reported vaccine doses and (b) patient age yielded a linear relationship with r 2 = 0.91 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 24 publications
0
29
0
4
Order By: Relevance
“…The reason for hospitalization and the age of the child at the time were not determined, but the latter finding appears consistent with a study of 38,801 reports to the VAERS of infants who were hospitalized or had died after receiving vaccinations. The study reported a linear relationship between the number of vaccine doses administered at one time and the rate of hospitalization and death; moreover, the younger the infant at the time of vaccination, the higher was the rate of hospitalization and death [55]. The hospitalization rate increased from 11% for 2 vaccine doses to 23.5% for 8 doses (r 2 = 0.91), while the case fatality rate increased significantly from 3.6% for those receiving from 1-4 doses to 5.4 % for those receiving from 5-8 doses.…”
Section: Discussionmentioning
confidence: 97%
“…The reason for hospitalization and the age of the child at the time were not determined, but the latter finding appears consistent with a study of 38,801 reports to the VAERS of infants who were hospitalized or had died after receiving vaccinations. The study reported a linear relationship between the number of vaccine doses administered at one time and the rate of hospitalization and death; moreover, the younger the infant at the time of vaccination, the higher was the rate of hospitalization and death [55]. The hospitalization rate increased from 11% for 2 vaccine doses to 23.5% for 8 doses (r 2 = 0.91), while the case fatality rate increased significantly from 3.6% for those receiving from 1-4 doses to 5.4 % for those receiving from 5-8 doses.…”
Section: Discussionmentioning
confidence: 97%
“…Goldman and Miller [96] have previously examined the VAERS database, specifically looking at hospitalization rates and mortality statistics as a function of the number of vaccines simultaneously administered and of age. Linear regression analysis revealed several statistically significant trends, including a positive correlation between hospitalization rates and number of vaccine doses.…”
Section: Other Related Workmentioning
confidence: 99%
“…Brachial neuritis afflicts up to 10 of every million tetanus vaccinees [7]. The Centers for Disease Control and Prevention (CDC) in the U.S. recommended 26 vaccine doses for infants in 2007 with clinical implications suggesting deleterious impacts on infants' health due to uncharacterized interference among unrelated vaccines after consecutive cycles of intensive immunization [8]. All measlescontaining vaccines are associated with several types of adverse events, including seizure, fever, and immune thrombocytopenia purpura [9].…”
Section: Anti-vaccine Movements Fueled By Vaccines' Incertitudementioning
confidence: 99%